Finding Correlations Between mRNA and Protein Levels in Leishmania Development: Is There a Discrepancy? - Cortazzo da Silva, Leonardo; Aoki, Juliana Ide; Floeter-Winter, Lucile Maria (Frontiers in Cellular and Infection Microbiology, 2022)
Multiple genes and proteins have been identified as differentially expressed in the stages of the Leishmania life cycle. The differentiation processes are implicated in specific transcriptional and proteomic adjustments driven by gene expression regulation mechanisms. Leishmania parasites lack gene-specific transcriptional control, and gene expression regulation mostly depends on posttranscriptional mechanisms. Due to the lack of transcriptional regulation, criticism regarding the relevance of transcript quantification as a possible and efficient prediction of protein levels is recurrent in studies that use transcriptomic information. The advent of high-throughput technologies has improved the analysis of genomes, transcriptomes and proteomes for different organisms under several conditions. Nevertheless, defining the correlation between transcriptional and proteomic profiles requires arduous and expensive work and remains a challenge in Leishmania. In this review, we analyze transcriptomic and proteomic data for several Leishmania species in two different stages of the parasite life cycle: metacyclogenesis and amastigogenesis (amastigote differentiation). We found a correlation between mRNA and protein levels of 60.9% and 69.8% for metacyclogenesis and amastigogenesis, respectively; showing that majority mRNA and protein levels increase or decrease concomitantly. Among the analyzed genes that did not present correlation indicate that transcriptomic data should be carefully interpreted as protein expression. We also discuss possible explanations and mechanisms involved for this lack of correlation.